Procedural and clinical outcomes of type 0 versus type 1 bicuspid aortic valve stenosis treated with transcatheter valve replacement: insights from the BEAT international collaborative registry. (25th November 2020) - Ielasi, A; Moscarella, E; Mangieri, A; Tchetche, D; Kim, W; Pagnesi, M; Sinning, J.M; Landes, U; Kornowski, R; De Backer, O; Nickenig, G; De Biase, C; et al.
Abstract: Background: Transcatheter aortic valve replacement (TAVR) is an established therapy for symptomatic severe aortic stenosis. Bicuspid aortic valves (BAV) were generally excluded from randomized trials due to anatomic features that may challenge TAVR (valve morphology, annulus geometry and size and severe calcifications). Nevertheless real-world registries have shown that a consistent number of BAV has been treated with TAVR. Whether BAV phenotype may affect acute or long-term outcomes following TAVR still remains unclear. Purpose: Evaluate the impact of BAV phenotype on procedural and clinical outcomes after TAVR with new generation valves. Methods: Patients included in the BEAT (Balloon vs Self-Expandable valve for the treatment of bicuspid Aortic valve sTenosis) registry were classified according to the BAV phenotype. Procedural and clinical outcomes of type 0 (2 cusps, 1 commissure, no raphe) vs type 1 (1 raphe) BAV are here reported. Primary endpoint was post-procedural device success, according to Valve Academic Research Consortium–2 (VARC-2) criteria. Secondary endpoints included procedural complications, rate of permanent pacemaker (PM) implantation and assessment of clinical outcomes at 30-day and 1-year follow-up. Results: BAV 0 phenotype was present in 25 (7.1%) cases, and BAV 1 in 218 (61.8%). 3 (0.9%) patients with BAV 2 phenotype and 105 (29.8%) patients in whom BAV phenotype was undeterminable were excluded. Baseline characteristics of the two populations were well balanced. Mean STS score tended to be lower in type 0 vs type 1 BAV (3.35% ±1.8 vs 4.5% ± 3.0, p=0.062). Mean transvalvular gradient, aortic valve area (AVA), and left ventricular ejection fraction didn't differ between groups. According to CT findings moderate-severe aortic valve calcifications were less frequently present in type 0 vs type 1 (52% vs 71.1%, p=0.01). TAVR was performed under conscious sedation in most patients (89.7%), no differences were noted in terms of valve type, valve size, pre and postdilation between groups. There was no significant difference in any peri-procedural complication including pericardial tamponade, second valve implantation, valve embolization, annular rupture, aortic dissection, coronary occlusion, conversion to open surgery, and need of PM between groups however VARC-2 success tended to be lower in type 0 BAV versus type 1 (72% vs 86.7%; p=0.07). A higher rate of mean transvalvular gradient>20 mmHg was observed in the type 0 vs type 1 groups (respectively 24% vs 6%, p=0.007), while no differences were reported in the rate of moderate-severe aortic regurgitation. At 30-day and 1-year follow-up we did not find differences in clinical outcomes. Conclusions: Our study confirms the feasibility of TAVR in both type 0 and type 1 BAV, however despite a lower rate of moderate-severe calcifications, a trend toward a lower VARC device success and a higher rate of mean transvalvular gradient >20 mmHg was observed in type 0 vs type 1 BAV. Funding Acknowledgement: Type of funding source: None